Specification of Subject of Reader’s Query : Reader-Computer Dialogue. (Non-conventional Methods in Document Retrieval. 20) - Neelameghan, A. (Journal of Information and Knowledge, 1972)
Reader’s query statement may not specify coextensively the subject of his interest at the moment. He may approach the document finding system by the name in the natural language of any one of the component ideas of the subject he may be interested in at the moment. The document finding system should have the built-in facility to enable the reader enter the system via the name of the component idea he brings up; help him recall other component ideas he may be interested in; help him to formulate the subject coextensively given only some of its fragments; help him structure and express the subject of his interest at the moment in the same manner as the subjects of documents have been structured and expressed; and present to him in a small range of scanning ail the entries for the documents on the subject of his interest at the moment. The features of S R Ranganathan’s document finding system model, which provides these facilities, are briefly described. The need for a dialogue between reader, documentalist, and document finding system in specifying the subect of reader’s query is Indicated. Two methods of conducting this dialogue between the reader and the computer in a computer-based document finding system are described. The method developed earlier displays to the reader parts of the schedules and the alphaoeticai index to it in the scheme for classification used ana the dialogue is based on this. In the second method, appropriate parts of the alphabetical index to the subjects of the documents in the main part of the catalogue-on-tape is used. The alphabetical index is derived by the POPSI method Postulate-based Permuted Subject Indexing System. The relative advantages of the latter method and ita likely impact on the design of document finding systems are indicated.